Caridina simoni Bouvier, 1904 (Crustacea: Decapoda: Caridea: Atyoidea: Atyidae) and the synonymy by Johnson, 1963 - Richard, Jasmine; Clark, Paul F. (Zootaxa, 2014)
Johnson (1963) attempted to review the ‘Caridina nilotica complex’ established by Bouvier (1925) and as a result considered several distinct freshwater shrimp species from Indo-West Pacific region as junior synonyms of C. simoni Bouvier, 1904. However, Tiwari and Pillai (1971) indicated the need to clarify the taxonomical status of the many synonyms created by Johnson (1963). Therefore, type and non-type specimens were examined for the present study including C. simoni Bouvier, 1904, C. gracilipes De Man, 1908, C. peninsularis Kemp, 1918, C. mccullochi J. Roux, 1926, C. meridionalis J. Roux, 1926 and C. novaecaledoniae J. Roux, 1926. These species were re-described, illustrated and their taxonomic status confirmed. The type series of C. mccullochi and C. meridionalis was found to comprise a number of already described Caridina species. In addition, three undescribed species were discovered in a series of specimens identified as C. meridionalis and one in material assigned to C. mccullochi.